Poder calórico de la madera y del carbón procedente de plantaciones de diferentes edades de Simarouba amara Aublet “marupa” y Cedrelinga cateniformis Ducke “tornillo”, Puerto Almendras, Iquitos, Perú - Acho Zevallos, Yury Gilberto (2013)
In order to determine the calorific value of wood and charcoal from demonstration plantations of S imarouba amara "marupa" and C edrelinga cateniformis "tornillo", plantations of >15 to 20 years, >20 to 25 years, >25 to 30 years and >30 to 40 years of established in the CIEFOR Puerto Almendra of the UNAP were evaluated. Iquitos, Peru. The tests were carried out according to the specifications of the Brazilian Technical Standard 1985, Test Method N° NBR 8112, Metrology System, Standardization and Industrial Quality. The results show the calorific value of S. amara wood increases by 5243.30 kcal/kg; 5271.89 kcal/kg; 5306.00 kcal/kg and 5329.85 kcal/kg; similarly occurs in C. cateniformis wood by 5238.10 kcal/kg; 5725.00 kcal/kg; 5737.91 kcal/kg and 5744.66 kcal/kg in plantations of >15-20 years, of >20-25 years of >25-30 years and >30- 40 years, that is, in both plantations there is a direct relationship between the calorific value of the wood and the age of the plantation; while the calorific value in coal of S. amara is 6722.82 kcal / kg in plantation of >15-20 years and in coal of C. cateniformis is 6518.26 kcal / kg in plantation of >30-40 years.